Social support and quality of life among chronically homeless patients with schizophrenia - Chen, Jinliang; Song, Hongli; Li, Shuchun; Teng, Ziwei; Su, Yuhan; Chen, Jindong; Huang, Jing (Frontiers in Psychiatry, 2022)
This study aimed to describe the sociodemographic characteristics, social support received, and quality of life of chronically homeless patients with schizophrenia in China. A self-prepared sociodemographic questionnaire, the Social Support Rating Scale (SSRS), European Five-dimensional Health Scale (EQ-5D), and Eysenck Personality were administrated to 3,967 chronically homeless and 3,724 non-homeless patients from the Department of Xiangtan Fifth People’s Hospital, Hunan, China, between April 2011 and October 2016. Results indicated that the homeless patients were more likely to live outside the city and be ethnic minorities compared with non-homeless patients. Although the married proportion was higher among homeless patients, they had a higher rate of being divorced or widowed. Notably, the homeless patients had higher employment rates before illness, despite significantly lower education (P<0.001). Chronically homeless patients with schizophrenia showed a lower score in the SSRS (30.29±7.34 vs 26.16±10.04, p<0.001); they had significantly lower objective support, subject support, social support, and EQ-Visual Analogue Scale, Eysenck Personality Questionnaire-Psychoticism, and Eysenck Personality-Neuroticism scores (p<0.001). Homeless patients may be worse off, and could be assisted by providing accommodation, family intervention, medical services (such as pain medication), and other comprehensive measures.